Chemical Composition of Red Banana (Musa acuminata) Peeled and Unpeeled - Iniubong Abasiodiong Thomas, Ph.D; Professor Nkoyo Isong (Zien Journals, 2023)
The study examined chemical composition of Peeled Red Banana Flour (PRBF) and Unpeeled Red Banana Flour (URBF). The aim of the study was to process and assess the nutrient potentials of red banana and discover the nutrient content of red banana peel. Red banana was purchased from Akpan Andem market in Uyo Local Government Area of Akwa Ibom State. Processed and milled to flour both peeled and unpeeled. The result of proximate composition moisture, ash, fiber, protein, CHO of PRBF showed 1.63 ± 0.02%, 7.22 ± 0.07, 6.17 ± 0.04, 6.36 ± 0.78, 78.08 ± 0.45 respectively while URBF were 1.17 ± 0.15%, 9.04 ± 0.07, 7.39 ± 0.04, 7.53 ± 0.02%, 73.89 ± 0.35 respectively. The result of the antinutrient (HCN, Oxalate, phytate and tannin) of PRBF 0.41 ± 0.00 mg / 100 g, 14.33 ± 0.00, 292.63 ± 0.06, 3.69 ± 0.00 respectively while URBF were 1.08 ± 0.00, 20.21± 0.00, 274 ± 0.71, 12. 99 ± 0.00 respectively. The values obtained for micronutrient (Calcium, iron, vitamin A and C) of PRBF were 72.05 ± 0.00, 0.01 ± 0.00, 0.07 ±0.00, 11.82 ± 0.01 respectively while URBF were 80.30 ± 0.00, 0.00 ± 0.00, 0.19 ± 0.00 and 14. 80 ± 0.02 respectively. The result implies that red banana can supply a essential nutrient required for various body functions and the peel is good source of vitamin A, C and calcium significantly higher (p ˃ 0.005) than PRBF. The result of the study showed that red banana is low in iron 0.00 ±0.00. The banana peel is a good source of calcium, vitamin A and vitamin c.
Keywords: Chemical Composition; Red Banana; Peeled and Unpeeled